The inheritance pattern for the dwarf phenotype in hybrids from crosses among sunflower lines differing in alleles of the Rht1 locus - I. N. Anisimova; G. V. Khafizova; L. G. Makarova; N. V. Alpatieva; M. K. Ryazanova; O. M. Borisenko; V. A. Gavrilova (Труды по прикладной ботанике, генетике и селекции)
Background. Sunflower seed production is based on utilization of the heterosis effect, manifesting itself in improving both yield and plant height in hybrids. Short-stemmed lines need to be used to develop commercial hybrids with an optimum height. Molecular bases of the trait manifestation in the dwarf lines from VIR’s sunflower genetic collection have not yet been studied. Materials and methods. The material included 27 short-stemmed and 10 tall sunflower lines from VIR’s genetic collection, as well as the F1 and F2 hybrid generations derived from crossing the tall (VIR 340) and dwarf (VIR 171) genotypes. The parental lines and hybrids were phenotyped for plant height, leaf number, and internode length. Genotyping for the Rht1 locus (HaDella1 candidate gene), encoding the negative regulator of the gibberellin response, the DELLA protein, was performed using the developed CAPS marker. Results. The average plant height in the VIR 340 line over a three-year study was 162 cm, the number of leaves 29, and the internode length 6 cm. The VIR 171 line demonstrated the plant height of 66 cm, leaf number of 24, and internode length of 2.8 cm. The F1 hybrids were uniform, with the height of 180–190 cm, that indicated the dominance of the long stem trait. Analyzing the segregation in the F2 hybrid generation led to an assumption admitting the digenic control of the dwarf phenotype in the VIR 171 line. The CAPS marker G-D-1/ Bmt I was developed to identify a missense mutation T>C in the first exon of the HaDella1 gene, which results in the substitution of leucine with proline in the DELLA motif. Using the marker, the mutant Rht1 allele was identified in the VIR 171 and VIR 434 dwarf lines, similar in their origin and phenotype. The results of validation in the F2 hybrid population (VIR 340 × VIR 171) confirmed the efficiency of the G-D-1 / Bmt I marker for selecting dwarf genotypes homozygous for the Rht1 mutant allele.